Comparison of Quality of Life and Depression among Women with Normal and High Risk Pregnancies - M Mirmohammadaliei; Z Khakbazan; A Kazemnejad; F Abbaszadeh (Tehran University of Medical Sciences, 2007)
Background & Aim: Women with high risk pregnancy experience changes in their personal, family, and social life that affect their quality of life and mental status. The aim of this study was to determine the effect of type of pregnancy (normal or high risk) on quality of life and depression levels in pregnant women.Methods & Materials: In this case-control study, a total of 100 women (50 women with normal pregnancies and 50 women with high risk pregnancies) who referred to the prenatal clinics of Kashan Medical University were studied. Subjects were randomly selected and then allocated in the normal (control) or high risk (case) groups. Data were gathered using a three-part questionnaire that included demographic characteristics, the Short Form 36 Health Survey (SF-36) to assess the quality of life, and the Beck Depression Inventory (BDI) to assess the levels of depressive symptoms.  Results: In this study, the results revealed that the mean score of the quality of life was lower in the women with high risk pregnancy (53/20±16/83) in comparison with the women with normal pregnancy (62/18 12/48). The mean of the BDI scores in high risk pregnancies (15/34±9/15) were significantly higher than in normal pregnancies (9/8±5/44). Depression has strong negative correlation with quality of life in both women with high risk and normal pregnancies (P<0.001).Conclusion: To sum up, it is very important to identify women that are at risk and help them to promote their quality of life.